2014
DOI: 10.4067/s0717-92002014000300011
|View full text |Cite
|
Sign up to set email alerts
|

Selección de funciones de distribución de frecuencias diamétricas, para Pinus taeda, Eucalyptus globulus y Eucalyptus dunnii en Uruguay

Abstract: SUMMARYThe aim of this study was to compare the accuracy of Weibull, reverse Weibull, S B Johnson, Gamma and Beta distributions, fitted with the method of moments and maximum likelihood, for describing diameter distributions in stands of Pinus taeda, Eucalyptus globulus, and Eucalyptus dunnii in Uruguay. Data from 429 permanent plots of P. taeda, 185 plots of E. globulus and 271 plots of E. dunnii were used. To compare the quality of fit for the probability distribution function (pdf), the Kolmogorov-Smirnov a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Estos resultados del mejor ajuste de la función de Weibull se corresponden con los encontrados por Ferrere et al (2001) para P. caribaea var. caribaea en Argentina así como para otras especies de Pinus como: P. pinaster por Álvarez & Ruiz (1998) en Galicia, España; P. pinea por Nanos (2002) en Valladolid, España; en plantaciones de P. durangensis, P. engelmannii, P. cooperi, y P. arizonica por Maldonado & Návar (2002) en Durango México y para P. patula por Santiago et al (2014) en la región de Zacualtipán, Hidalgo, México; así como con los encontrados en plantaciones de P. taeda por Hirigoyen & Rachid (2014) en Uruguay, por Rubio et al (2015) para parcelas permanentes de Pinus, Juniperus y Quercus en Nuevo León, México. Además, estos resultados discrepan con los encontrados para la especie por Montalvo et al (1992) quienes encontraron como función de mejor ajuste la de Gauss.…”
Section: Discussionunclassified
“…Estos resultados del mejor ajuste de la función de Weibull se corresponden con los encontrados por Ferrere et al (2001) para P. caribaea var. caribaea en Argentina así como para otras especies de Pinus como: P. pinaster por Álvarez & Ruiz (1998) en Galicia, España; P. pinea por Nanos (2002) en Valladolid, España; en plantaciones de P. durangensis, P. engelmannii, P. cooperi, y P. arizonica por Maldonado & Návar (2002) en Durango México y para P. patula por Santiago et al (2014) en la región de Zacualtipán, Hidalgo, México; así como con los encontrados en plantaciones de P. taeda por Hirigoyen & Rachid (2014) en Uruguay, por Rubio et al (2015) para parcelas permanentes de Pinus, Juniperus y Quercus en Nuevo León, México. Además, estos resultados discrepan con los encontrados para la especie por Montalvo et al (1992) quienes encontraron como función de mejor ajuste la de Gauss.…”
Section: Discussionunclassified
“…For the young input data, the number of plots that did not present adherence rose to a total of 41. Hirigoyen & Rachid (2014), while evaluating Uruguayan P. taeda, also applied the Weibull probability density function using the method of moments and reported that 5.3% of the plots did not present adherence to the observed Table 4. Initial parameters and goodness of fit for the models of the prognosis system for loblolly pine (Pinus taeda) (1) .…”
Section: Resultsmentioning
confidence: 99%
“…For Uruguay, some studies on model sets for P. taeda have been published, which include volume and taper equations , diametric frequency distribution functions (Hirigoyen & Rachid, 2014), and several mensurational relationships, such as height to diameter at breast height (DBH), crown diameter to DBH, crown volume to DBH, bark thickness to DBH, and bark thickness to tree height (Leites et al, 2013).…”
Section: Introductionmentioning
confidence: 99%